2023
DOI: 10.1002/adma.202210789
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid “Water Pocket” for Stable and Environment‐Adaptable Aqueous Zinc Metal Batteries

Abstract: The strong reactivity of water in aqueous electrolytes toward metallic zinc (Zn), especially at aggressive operating conditions, remains the fundamental obstacle to the commercialization of aqueous zinc metal batteries (AZMBs). Here, a water‐immiscible ionic liquid diluent 1‐ethyl‐3‐methylimidazolium bis(fluorosulfonyl)amide (EmimFSI) is reported that can substantially suppress the water activity of aqueous electrolyte by serving as a “water pocket”, enveloping the highly active H2O‐dominated Zn2+ solvates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Furthermore, current research on zinc batteries is usually conducted in an ideal conditions, which cannot represent the actual working conditions for stationary storage. 7 The balance of cathodes and anodes in terms of charge and a high areal capacity of over 2 mAh/cm 2 should be taken into account but is often ignored.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, current research on zinc batteries is usually conducted in an ideal conditions, which cannot represent the actual working conditions for stationary storage. 7 The balance of cathodes and anodes in terms of charge and a high areal capacity of over 2 mAh/cm 2 should be taken into account but is often ignored.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Coupling nonflammable aqueous electrolytes with zinc metal anodes, ZIBs present fast kinetics and high safety. , However, ZIBs do not satisfy the market demands since zinc metal anodes suffer from moderate irreversibility during repeated zinc stripping and plating processes. , Corrosion of zinc at the interface, mainly due to the active water corrosion and its related low coulombic efficiency (CE), are the main drawbacks in developing zinc anodes, especially at high utilization. Furthermore, current research on zinc batteries is usually conducted in an ideal conditions, which cannot represent the actual working conditions for stationary storage . The balance of cathodes and anodes in terms of charge and a high areal capacity of over 2 mAh/cm 2 should be taken into account but is often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In order to illustrate the attraction of CMC molecules to H 2 O solvent molecules, a ball-stick model of CMC with molecular weight n = 8 was established and the oxygen next to sodium ions was defined as terminal O, with 16 of them (Figure S11, Supporting Information). [33] Moreover, as shown in Figure 2c, radial distribution functions (RDFs) g(r) and coordination numbers [22] As shown in Figure 2d, the formation process of the gradient was observed by colliding 4 m ZnSO 4 @CMC electrolyte (black) with 1 m red ZnSO 4 electrolyte (optical images seen in Figure S14, Supporting Information) on a glass sheet. During the short time, the two are in contact, they quickly diffuse into each other and remain stable after about 5 minutes.…”
Section: Using Aqueous Cmc Binder To Stabilize Gradientmentioning
confidence: 89%
“…Up to now, the longest reported zinc anode coated by indium metal (In@Zn) had a cycle life of over one year (9400 h at 1 mA cm −2 for 0.5 mAh cm −2 ). [16] The regulation of the electrolyte [19] includes adjusting the concentration of the electrolyte (1, 2, 3 m), using different zinc salts (ZnSO 4 , ZnCl 2 , [20] Zn((CF 3 SO 3 ) 2 [21] ), different electrolyte additives (ionic liquid diluent 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)amide, [22] silk fibroin, [23] and acetic acid [24] ), SEI layer, [25] and the use of gel electrolytes. [26] Experience has shown that the deposition morphology of zinc is strongly influenced by electrolyte concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the IL induced a great conductivity and outstand-ing electrolyte infiltration. [117,118] The Zn-ion/polysulfide battery was reversible owing to the CF 3 SO 3 − anions in the IL synergistically. The S cathode was constructed through the chemical bonding between carbon cloth and a copolymer, which presented binder-free and conductive properties.…”
Section: Electrode Engineeringmentioning
confidence: 99%